The Identification of Village and Tourism Potentials in Facing Economic Social Threats of Communities in Peatland - Ashaluddin Jalil; Yesi Yesi; Seger Sugiyanto (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2021)
Vulnerability to the forest and land fires in the Tohor River began in 2007 and 2009 due to the construction of canals for village development as well as the canalization of sago companies, which are 5-7 meters wide. The purpose of the study identified potential resources for people's lives and peatland protection. Data collection using observations, interviews, and discussion forums. The results showed that the potential in the field of natural resources consists of plantations including sago, rubber, river fisheries, honey, and natural forest vegetation. In addition, the economic potential is also very large individuals and groups have implemented the management of sago derivative products such as sago sugar, sago noodles, sago rendang, sago amplang, and various handicrafts from sago such as rumbia roofs, bags and mats. In the field of human resources, there are LPMP village institutions, PKK and KKP, Environmentally Conscious Group, Tohor River Youth, Fish Farming Group, and community network including sago farming groups and youth associations. The productive age group is also quite large but they generally work a lot in Malaysia as contract workers. The potential of Natural Resources and Human Resources is important in people's lives especially to protect peat but the potential has not been developed to the maximum. Collaboration from stakeholders is required to develop optimally the potential available for better peat life and ecosystem